THE EFFECT OF PRICE AND PROMOTION ON SHRIMP PETIS PURCHASE DECISION (CASE STUDY OF UD. DUA PUTRA JAYA GRESIK) - Nur Farida; Moh. Syukur Setiobudi (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to examine and prove the influence of price and promotions on puchasing decision of shrimp paste UD. Dua Putra Jaya Gresik. This study uses a quantitative approach with multiple linear regression analysis. The number of samples taken was 50 respondents and data collection was done by distributing questionnaires. The results showed that prices had a positive and significant influence on the increase in purchasing decisions for shrimp paste at UD. Dua Putra Jaya Gresik. Then the promotion has a positive and significant effect on purchase decisions to purchase shrimp paste at UD. Dua Putra Jaya Gresik. Prices and promotions simultaneously have a positive and significant effect on the increase in purchasing decisions for shrimp paste at UD. Dua Putra Jaya Gresik.